Quality Control System for ABK Inclusion Education - Nurhasan, Nurhasan; Madhakomala, R. (PT FORMOSA CENDEKIA GLOBAL, 2023)
Parents who have children with special needs are often worried about the future of their children with special needs. In inclusive school programs, dedicated teaching and support are provided to students who need help. Preventing discriminatory behavior, proper education, and equal access to multiple aspects of life are the goals of inclusive education. This study uses a literature review model by analyzing relevant articles and focusing on quality control in inclusive education for children with special needs. The implementation of inclusive education has several quality requirements that must be guaranteed in order to achieve the desired level of education and the success of inclusion education itself. Therefore, stakeholders need to evaluate inclusive education. Stakeholders can utilize the CIPP model assessment across various domains, including education, management, and enterprises, as well as at different hierarchical levels, such as projects, programs, or institutions. By upholding or enhancing the standards and effectiveness of inclusive education, the success rate in advancing education for children with special needs will naturally grow.